The Effect of Competence, Job Satisfaction, and Work Environment on Employee Performance - Rahmaini, Andy Dhifa Nur; Nianty, Dara; Zaeni, Nurhaeda (LifeSciFi, 2026)
Effective healthcare delivery relies heavily on the performance of hospital staff. This study investigates the influence of competence, job satisfaction, and work environment on employee performance, where operational challenges such as competency gaps, incentive disparities, and facility constraints hinder service quality and accreditation compliance. The primary objective is to analyze the individual and simultaneous effects of these factors while identifying the most dominant predictor to inform human resource strategies in healthcare settings. A quantitative explanatory approach was employed, collecting data from 111 permanent employees via a five-point Likert-scale questionnaire. Multiple linear regression analysis was conducted after validating instruments and confirming classical assumptions. Results reveal that all three variables positively and significantly affect performance, with competence exhibiting the strongest influence, followed by work environment and job satisfaction. The model explains 42.2 percent of performance variance. As implication, targeted interventions in training, rewards, and infrastructure are essential to enhance productivity and patient-centered care, offering actionable insights for hospital management and broader health system improvements.